2009
DOI: 10.1002/app.30689
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of a poly(vinyl chloride) composite filled with poly(methyl methacrylate) grafted to oil palm empty fruit bunches

Abstract: The influence of oil palm empty fruit bunch (OPEFB) fiber and oil palm empty fruit bunches grafted with poly(methyl methacrylate) (OPEFB-g-PMMA) on the tensile properties of poly(vinyl chloride) (PVC) was investigated. The OPEFB-g-PMMA fiber was first prepared with the optimum conditions for the grafting reaction, which were determined in our previous study. To produce composites, the PVC resin, OPEFB-g-PMMA fiber or ungrafted OPEFB fiber, and other additives were first dry-blended with a laboratory blender be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Currently, a number of studies have been conducted by different researchers on the 'zero waste' concept (Zaman 2013a). In Malaysia, several different approaches have been attempted to explore the potentials for reusing empty fruit bunches as main feedstocks or substrates to produce activated carbon (Firoozian et al 2011), bioethanol (Abu Bakar et al 2012), biohydrogen (Chong et al 2013), bio-oil (Abdullah et al 2010), biochar (Samsuri et al 2014), citric acid (Alam et al 2010), composite (Bakar et al 2010), lignophenol (Abdullah et al 2009), xylose (Tan et al 2013) and others. As empty fruit bunches contain high organic matter and mineral contents, these wastes are also currently being investigated as potential feedstocks in composting (Kananam et al 2011;Mohammad et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of studies have been conducted by different researchers on the 'zero waste' concept (Zaman 2013a). In Malaysia, several different approaches have been attempted to explore the potentials for reusing empty fruit bunches as main feedstocks or substrates to produce activated carbon (Firoozian et al 2011), bioethanol (Abu Bakar et al 2012), biohydrogen (Chong et al 2013), bio-oil (Abdullah et al 2010), biochar (Samsuri et al 2014), citric acid (Alam et al 2010), composite (Bakar et al 2010), lignophenol (Abdullah et al 2009), xylose (Tan et al 2013) and others. As empty fruit bunches contain high organic matter and mineral contents, these wastes are also currently being investigated as potential feedstocks in composting (Kananam et al 2011;Mohammad et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This impact strength of grafted composites' reduction was slightly higher compared to the ungrafted composite, even though a previous article reported that the slight improvement in tensile elongation at break provided a good indication of the improvement of impact strength [17]. This circumstance can be explained by the failure mode of the composites, whereby the composte is influenced by the strength of interface adhesion.…”
Section: Impact Strengthmentioning
confidence: 75%
“…The use of poly (methyl methacrylate)-grafted-oil palm empty fruit bunch or PMMA-g-OPEFB in poly(vinyl chloride) (PVC) has also been reported in our previous work [17]. The tensile properties of the grafted composite were influenced mainly by the fiber=matrix interaction.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations